Reliability of the Second and Third Iterations of the Sensory–Motor Dysfunction Questionnaire in a Subclinical Neck Pain Population - Ushani Ambalavanar; Heidi Haavik; Nitika Kumari; Imran Amjad; Nooshin Khobzi Rotondi; Bernadette Ann Murphy (Brain Sciences)
Background/Objectives: This study aimed to address limitations of the pilot reliability study on the Sensory–Motor Dysfunction Questionnaire (SMD-Q) in two parts. Part 1 evaluated the intra-rater reliability of SMD-Q version 2 (V2). Part 2 addressed V2’s limitations before assessing the intra-rater reliability of version 3 (V3). V2 framed questions as “over the past week”, whereas V3 also framed questions as “in a typical/usual week”. Methods: The SMD-Q was administered via QualtricsTM at baseline and 4 to 7 days later to subclinical neck pain participants, 51 in part 1 (32 F; mean age ± SD: 21.17 ± 2.66 y) and 27 in part 2 (20 F; mean age ± SD: 21.89 ± 2.81 y). Reliability statistics (quadratic weighted kappa (Kw) and Cronbach’s alpha (α)) were calculated for all items (V2) and total scores (V2 and V3). Results: There was excellent agreement for V2 total scores (Kw ≥ 0.75), and V3 total scores for “in a typical/usual week” (Kw ≥ 0.75), but fair to good agreement for V3 total scores of “over the past week” (0.40 < Kw < 0.75). V2 had acceptable (0.7 ≤ α < 0.8) to good internal consistency (0.8 ≤ α < 0.9), while V3 had good internal consistency for both administrations. Conclusions: Versions 2 and 3 of the SMD-Q appear to reliably capture disordered sensorimotor integration in people with subclinical neck pain, with improved reliability in V3 when questions are framed as “in a typical/usual week”. However, further research is needed to confirm this finding.